Adopting the EURO in Romania - ŞIMON, Ilie (Annals of Spiru Haret University. Economic Series, 2011)
This paper addresses the adoption of the Euro currency in 2014, as estimated in the National Programme. Based on the convergence criteria analysis on the current national background, we can foresee an earlier monetary integration.